Accessibility for Low-Income Workers in New Orleans, Louisiana, after Hurricane Katrina. Issue 1 (January 2014) - Lowe, Kate
Existing research has identified the transportation challenges that low-income workers face, including a spatial mismatch between suburban entry-level jobs and urban low-income earners. Because most studies rely on travel models and secondary data, such studies may not capture the experiences of low-income workers. To understand better the mobility patterns and accessibility as they are experienced, this analysis explored commute choices and accessibility from the perspectives of low-income workers. The findings were based on open-ended surveys with 50 low-income workers in New Orleans, Louisiana, and its inner suburbs. For many workers (40%), transportation problems did not limit job opportunities. African-American and centrally located respondents most commonly did not perceive transportation as a barrier to employment. Almost all respondents cited transportation problems for some locations or activities, particularly shopping. The loss of a functional automobile was a common reason to change commute mode after Hurricane Katrina; this situation indicates that low-income workers may shift in and out of car ownership, as well as change home and job locations. The interviewees most frequently reported that automobile ownership would improve their mobility, and some interviewees desired increased bus frequency and reliability. The mixed findings on perceived job accessibility demonstrate the need to integrate transportation and workforce research and policy better, perhaps with special attention to race. In addition, more transportation research on perceptions and actual challenges, including the role of rigid work schedules, is needed. Finally, given the dynamic auto ownership status, employment sites, and residential patterns, more longitudinal study is needed.